2013
DOI: 10.1002/pros.22694
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer cells differ in testosterone accumulation, dihydrotestosterone conversion, and androgen receptor signaling response to steroid 5α-reductase inhibitors

Abstract: BACKGROUND Blocking 5α-reductase-mediated testosterone conversion to dihydrotestosterone (DHT) with finasteride or dutasteride is the driving hypothesis behind two prostate cancer prevention trials. Factors affecting intracellular androgen levels and the androgen receptor (AR) signaling axis need to be examined systematically in order to fully understand the outcome of interventions using these drugs. METHODS The expression of three 5α-reductase isozymes, as determined by immunohistochemistry and qRT-PCR, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 39 publications
4
38
1
Order By: Relevance
“…Although dutasteride was developed as a dual its 5α-reductase inhibitor, previous studies indicate that it can also directly inhibit AR activity (2628). Therefore, we considered that dutasteride might be functioning as a direct AR antagonist independent of its 5α-reductase inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…Although dutasteride was developed as a dual its 5α-reductase inhibitor, previous studies indicate that it can also directly inhibit AR activity (2628). Therefore, we considered that dutasteride might be functioning as a direct AR antagonist independent of its 5α-reductase inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…Further, while not conducted in muscle cells, intracellular androgen concentrations in cultured prostate cancer cells differ from those values observed in the surrounding culture media. When extrapolated to skeletal muscle, this suggests that measurement of hypogonadal or physiological concentrations of androgens in circulation may not be representative of those levels within skeletal muscle (Sedelaar and Isaacs, 2009, Wu, Godoy et al, 2013). …”
Section: 1 Androgensmentioning
confidence: 99%
“…Therefore, LC‐MS/MS was performed to determine if media composition impacted T metabolism. LAPC‐4 cells were used because LAPC‐4 cells express SRD5A enzymes that metabolize T to DHT (Figure A, modified from ), unlike LNCaP or C4‐2 cells, which cannot metabolize T to DHT . LC‐MS/MS revealed that LAPC‐4 cells cultured for 6 days in CM alone produced higher levels of DHT (all P ‐values <0.05; Supplemental Table S5) than LAPC‐4 cells cultured for 6 days in SFM or CSM alone (Figures B and C, and Supplemental Table S5).…”
Section: Resultsmentioning
confidence: 99%